Hegemonic Masculinity in Ghamad Shere (Persistent Shere) Directed by Hem Raj BC - Bista, Asmita (JODEM: Journal of Language and Literature, 2024)
Nepali film Ghamad Shere promotes hegemonic masculinity by presenting the central character as a struggling person, who overcomes every problem by ascertaining his masculinity. In Ghamad Shere, the central character, Sher Bahadur, appears as bold, aggressive, and industrious man. In the film, including Sher Bahadur, while exhibiting the so-called masculine power, the male characters involve in the competition to outsmart each other.  Thus, the paper aims to investigate how the practice of hegemonic masculinity has affected the life of males in Chhinchu village. It analyzes the problems the characters go through in their life caused by the imposition of conventional masculine roles and identities. This paper also assesses the reasons that force the males to perform the stereotyped gender roles. To analyze the film, R.W. Connell’s and Michael Kimmel’s idea of masculinity theory has been used as an approach. Kimmel and Connell argue that since the traditional gender roles are constructed, masculinity is a constructed entity that is achieved through constant performance. Revealing the gender practices in Chhinchu village, Ghamad Shere unfolds problems such as to leave the village for foreign country in search of employment, being cheated by their wives and the like, faced by the males of this village. The paper concludes that constrained to the normative gender roles, the males of this village keep their hegemonic masculinity intact.  The article further concludes that the male characters of this film encircle them to hegemonic masculinity because being part of that society, one hardly can escape from the socially enforced gender roles.